Wealth Effects and Earnings Premiums for Job Hazards - Viscusi, W. Kip (The Review of Economics and Statistics, 1978)
A DAM Smith (1937) observed that "the whole of the advantages and disadvantages of the different employments of labor and stock must, in the same neighborhood, be either perfectly equal or continually tending to equality."If a job poses health and safety risks that are especially great, a worker will require higher levels of compensation or greater non-pecuniary benefits in order for him to accept the risky job.Despite the fact that the theory of compensating differentials is almost two centuries old, it has been only recently that this theory has been subjected to successful empirical tests.'The purposes of this essay are twofold.First, in section II, I will formalize the theory of individual choice among potentially hazardous jobs for the general situation in which worker preferences are contingent on the health state outcome.An important implication of this analysis is that the job risk that a worker selects will be negatively related to his wealth.The second purpose of the investigation is to test the two principal conceptual hypotheses.The characteristics of the principal data source to be used are summarized in section III.The University of Michigan Survey of Working Conditions, which is the data set used in the compensating differentials analysis, provides very extensive information concerning the nature of the worker's particular job and his personal characteristics.Section IV presents the analysis of the earnings differentials generated by job hazards and other job attributes.In section V, I consider the responsiveness of the job risk to a worker's wealth.The empirical findings, which are consistent with the theoretical predictions, are summarized in section VI. II. Optimal Choice among Hazardous Job AlternativesRecent economic analyses of choices among potentially hazardous jobs have generalized Adam Smith's notion of compensating wage differentials to probabilistic contexts.The study by Oi (1973) views adverse job consequences as being tantamount to a drop in income.He concludes that jobs posing greater risks will command compensating wage differentials.A more detailed analysis along similar lines is presented by Thaler and Rosen (1976), who develop Oi's approach and also consider the situation in which individuals face lotteries on life and death.2The payoff after an adverse outcome (death) is represented by a bequest function.The approach taken here also can be viewed as a probabilistic generalization of the compensating differential analysis.It differs in that individuals' utility functions are assumed to be dependent on one's health state.The static model in this section illustrates the properties of the optimal job choice of a worker who is choosing from a set of job opportunities that involve the same number of work hours but have differing probabilities of an adverse consequence.3This approach does not impose assumptions that are unduly restrictive since most job opportunities offer little individual leeway in the choice of hours.